Effect of Bacteriophage Therapy on the Hemocyte Profile of Whiteleg Shrimp (Litopenaeus vannamei) Infected with Acute Hepatopancreatic Necrosis Disease - Takwin, Bagus Ansani (MARLIN, 2025)
Acute Hepatopancreatic Necrosis Disease (AHPND), caused by Vibrio parahaemolyticus, poses a major threat to the cultivation of Pacific white shrimp (Litopenaeus vannamei) due to its high mortality rate. This study aimed to evaluate the effectiveness of bacteriophage therapy on the non-specific immune response of shrimp, assessed through Differential Hemocyte Count (DHC) analysis. The research was conducted over six months using a Completely Randomized Design with seven treatment groups, including positive control (KP), negative control (KN), antibiotic treatment (KA), and three bacteriophage dosages: 10⁷ PFU/mL (FB7), 10⁸ PFU/mL (FB8), and 10⁹ PFU/mL (FB9), all challenged with V. parahaemolyticus at 10⁵ CFU/mL. DHC observations were carried out on days 0, 1, 3, and 7 post-treatment. The results indicated that the bacteriophage-treated group, particularly FB9 (10⁹ PFU/mL), maintained a hyaline cell proportion of 50–57% through day 7, similar to the immune profile of the negative control. In contrast, the positive control exhibited a marked decrease in hyaline cells and an increase in granular cells, indicating an immune response to infection. Bacteriophage application, especially at high dosage (FB9), effectively stimulated the shrimp's immune response by preserving hyaline cell levels, making it a promising eco-friendly alternative for AHPND control.